Assistance Innovation In Organic Waste Management As A Hydroponic Media Substrate Building A Green Future - Priyadi, Sapto; Suprapti, Endang; Soelistijono, R.; Haryuni, H.; Shodiq, Yusuf Nur; Nugroho, Benny; Alanusa, Awang; Kurnia Dewi, Tyas Soemarah; Achmad Fatchul Aziez; Daryanti; Mardhika Sari, Siti (Universitas Tunas Pembangunan Surakarta, 2024)
Organic waste management is becoming increasingly important in responding to current global environmental challenges. In this context, this community service aims to explore the potential for using organic waste as a substrate for hydroponic media in building a greener agricultural future in a sustainable system. The use of organic waste as a substrate for hydroponic media has great potential in supporting plant growth, because it contains available N, P2O5, K2O and C-organic nutrients which are sufficient for plant growth and development. Plants grown in organic waste-based substrates show comparable or even better growth compared to plants grown in conventional substrates. The use of organic waste in hydroponic farming also has a positive impact on the environment. More effective management of organic waste helps reduce environmental pollution and greenhouse gas emissions. This community service program has also succeeded in increasing public awareness and knowledge about organic waste management and hydroponic technology. Thus, the use of organic waste as a substrate for hydroponic media offers great potential in improving organic waste management, increasing agricultural productivity, and reducing negative impacts on the environment. This activity makes a real contribution to building a more sustainable agricultural future and contributes to global efforts in facing increasingly complex environmental challenges.